The Effect of Midazolam Sedation on Agitation Incidence in Post-Operative Patients Who Are Intubated in the ICU of Adam Malik General Hospital Medan - Adnani, Muhammad Ivanny; Irina, Rr Sinta; Zainumi, Cut Meliza (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2025)
Background: Agitation in critically ill patients is a phenomenon that can endanger patient safety and assistance during treatment in the intensive care unit (ICU). It is characterized by increased motor and mental activity that manifests as inappropriate behavior, disorganized thoughts, and loss of self-control over actions.Objective: Evaluating the effect of midazolam sedation on the incidence of agitation in post-operative intubated patients in the ICU at Adam Malik General Hospital, Medan.Methods: This is a retrospective analytical study with a cross-sectional design using a scoring approach to determine the relationship between midazolam use and agitation in postoperative patients intubated in the ICU after surgery at Adam Malik General Hospital, Medan. The subject selection technique used was non-probability sampling with a consecutive sampling method, where 115 subjects were needed. Bivariate analysis for numeric variables used the Independent T-test if the data were normally distributed, or the Mann-Whitney U test if the data were not normally distributed. The results of the analysis were said to be significant if p <0.05, with a confidence level of 95%.Result: The results of the study the dose of midazolam given to postoperative patients intubated in the ICU of Adam Malik General Hospital, Medan had a minimum dose of 0.017 mg/kg/hour, a maximum of 0.031 mg/kg/hour and an average of 0.023 mg/kg/hour which was related to the incidence of patient agitation during the ICU obtained a significant relationship p <0.05.Conclusion: The effect of midazolam sedation on the incidence of agitation in postoperative patients who were intubated in the ICU of Adam Malik General Hospital, Medan, patients who experienced agitation had a statistically significant difference in the dose of midazolam. And there were side effects of agitation in the form of release of invasive instruments/devices, such as endotracheal tubes, in patients who did not receive sufficient sedation.